High-gloss stain-resistant glaze, ceramic and preparation method thereof
By using raw materials and preparation methods for high-gloss and stain-resistant glaze water, the problem of poor coordination of gloss, stain-resistant and antibacterial properties of ceramic products is solved, and the high-gloss, stain-resistant, antibacterial, water-resistant and temperature-resistant stability of ceramic products is achieved.
Patent Information
- Application Number
- CN202411854904.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing ceramic products have poor coordination of gloss, stain resistance and antibacterial properties, and insufficient water resistance and temperature resistance stability, making it difficult to achieve integrated coordinated improvement.
High gloss and stain-resistant glaze water, including sodium feldspar, modified quartz powder, balance agent for blending sheet talc, calcite, nanoalumina, nanosilica and nanosilver oxide, are used to prepare high gloss and stain-resistant ceramics through ball milling and sintering technology.
It significantly improves the gloss, stain resistance and antibacterial properties of ceramic products, achieves performance coordination improvements, and enhances the product's water resistance and temperature resistance stability.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramics, and in particular to a high-gloss stain-resistant glaze, ceramics and a preparation method thereof. Background Art
[0002] Ceramics is a general term for pottery and porcelain. People invented pottery as early as the Neolithic Age about 8,000 years ago. Common ceramic materials include clay, alumina, kaolin, etc. Ceramic materials are generally hard but less plastic. In addition to being used in tableware and decoration, ceramics also play an important role in the development of science and technology. Ceramic raw materials are made from clay, a large amount of resources originally available on the earth, through quenching.
[0003] The glaze layer used in existing ceramic products has poor gloss performance, and the gloss and stain resistance of the products are poorly coordinated. At the same time, the antibacterial and long-lasting performance of the products is poor. It is difficult to achieve integrated and coordinated improvement of the products, and the products have poor water resistance and temperature change stability, which limits the product's use efficiency. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a high-gloss and stain-resistant glaze, ceramics and a preparation method thereof to solve the problems raised in the above-mentioned background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution:
[0006] The present invention provides a high-gloss stain-resistant glaze comprising the following raw materials in parts by weight:
[0007] 10-15 parts of albite, 8-12 parts of modified quartz powder, 6-9 parts of a balancing agent for blending flaky talc, 5-8 parts of calcite, 4-7 parts of nano alumina, 3-5 parts of nano silicon dioxide, 4-7 parts of nano silver oxide and 10-15 parts of water.
[0008] Preferably, the preparation method of the modified quartz powder is:
[0009] S11: The quartz powder is first stirred with a sufficient amount of a 5% by mass hydrogen peroxide solution, then washed with boiling water for 2-3 times, then filtered and dried, and preheated at 60-65° C. for 1 hour to obtain pretreated quartz powder;
[0010] S12: adding 1-3 parts by weight of a 4-6% sodium lignin sulfonate solution and 2-4 parts by weight of wollastonite to 6-9 parts by weight of a 5% sodium silicate solution, and then adding 1-2 parts by weight of stearic acid, stirring sufficiently, to obtain a wollastonite modified solution;
[0011] S13: Blending 4-7 parts of pretreated quartz powder and 6-10 parts of wollastonite modified liquid by weight, and continuing to stir sufficiently to obtain a quartz-based liquid;
[0012] S14: ultrasonically treat the quartz base liquid and the pyrophyllite / nano-titanium dioxide compounding agent in a weight ratio of 5:3. After the ultrasonic treatment is completed, filter and dry to obtain modified quartz powder.
[0013] Preferably, the ultrasonic power of the ultrasonic treatment is 450-550W, and the ultrasonic time is 1-2h.
[0014] Preferably, the preparation method of the pyrophyllite / nano-titanium dioxide compounding agent is:
[0015] According to weight, 5-8 parts of pyrophyllite and 1-3 parts of nano-titanium dioxide are added to 7-9 parts of sodium alginate solution, and then 2-4 parts of calcium nitrate solution and 1-2 parts of silane coupling agent KH550 are added, and the mixture is mixed thoroughly, filtered and dried to obtain a pyrophyllite / nano-titanium dioxide compounding agent.
[0016] Preferably, the mass fraction of the sodium alginate solution is 4-7%; the mass fraction of the calcium nitrate solution is 2-5%.
[0017] Preferably, the preparation method of the balancing agent for blending flaky talc is:
[0018] S101: mixing flaky talc, sodium dodecylbenzene sulfonate and chitosan solution in a weight ratio of (3-5):1:(6-8) to obtain a flaky talc solution;
[0019] S102: adding 3-5 parts of nano-mica powder and 2-3 parts of boron nitride to 5-8 parts of barium nitrate solution by weight, and then adding 1-3 parts of sodium carboxymethyl cellulose, and ball milling the mixture at a speed of 1000 r / min for 1 hour. After the ball milling is completed, filtering and drying are performed to obtain a formulation;
[0020] S103: stirring the blending agent and the flaky talc liquid in a weight ratio of 2:5, filtering and drying after the stirring is completed, to obtain a balancing agent for blending the flaky talc.
[0021] Preferably, the mass fraction of the chitosan solution is 2-5%; the mass fraction of the barium nitrate solution is 4-6%.
[0022] Preferably, the stirring temperature of the stirring treatment is 60-65° C., the stirring speed is 450-500 r / min, and the stirring time is 30-40 min.
[0023] The present invention also provides a method for preparing high-gloss stain-resistant ceramics, using the high-gloss stain-resistant glaze, comprising the following steps:
[0024] Step 1, weighing raw materials of high-gloss and stain-resistant glaze water according to weight parts, mixing the raw materials of high-gloss and stain-resistant glaze water and subjecting them to ball milling treatment, with a ball milling speed of 1000 r / min, and ball milling for 2 hours, and then completing the ball milling to obtain high-gloss and stain-resistant glaze water;
[0025] Step 2: 10-15 parts of illite, 5-8 parts of kaolin, 4-7 parts of potassium feldspar, 3-5 parts of silicon carbide and 2-5 parts of calcium carbonate are mixed by weight and wet-milled at a ball milling speed of 1500r / min for 2h. After sufficient ball milling, the mixture is put into a mold for molding at a molding pressure of 45-50MPa for 1h to obtain a ceramic body;
[0026] Step 3: glaze the ceramic body with high gloss and stain-resistant glaze water, with a glaze amount of 580g / m 2 Then, it is sintered at 1300°C for 2 hours. After the sintering is completed, a high-gloss and stain-resistant ceramic is obtained.
[0027] The invention also provides a high-gloss stain-resistant ceramic, which is prepared by the preparation method of the high-gloss stain-resistant ceramic.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The ceramic product of the present invention is glazed with high-gloss stain-resistant glaze water. The high-gloss stain-resistant glaze water is prepared by albite, calcite, nano-alumina, nano-silicon dioxide and nano-silver oxide. The gloss, stain resistance and antibacterial properties of the product are optimized through the coordination between the raw materials. At the same time, the modified quartz powder and the balancing agent for blending the flaky talcum powder cooperate with each other and adjust the effect together, thereby improving the coordination of product performance, and the product has remarkable water resistance and temperature change stability effects;
[0030] 2. Modified quartz powder: Quartz powder is treated with hydrogen peroxide solution, and then preheated at 60-65℃ for 1h to optimize the activity of quartz powder. At the same time, it is modified by stirring with wollastonite modification liquid. The sodium lignin sulfonate solution, wollastonite, 5% sodium silicate solution by mass and stearic acid in the wollastonite modification liquid are coordinated. The sodium lignin sulfonate solution is used as the matrix medium to enhance the interfacial activity between the raw materials. At the same time, wollastonite, sodium silicate solution and stearic acid are used to reinforce the quartz powder with needle-shaped wollastonite. At the same time, the raw materials in the wollastonite modification liquid are coordinated with each other to improve the quartz powder together, so that the obtained quartz matrix liquid can be in the system. Better cooperate with pyrophyllite / nano-titanium dioxide compounding agent, and optimize the coordination of system performance. The pyrophyllite / nano-titanium dioxide compounding agent uses pyrophyllite and nano-titanium dioxide as the base materials. Through the mutual cooperation of sodium alginate solution, calcium nitrate solution and silane coupling agent KH550, pyrophyllite has high temperature resistance, and nano-titanium dioxide can stimulate calcium nitrate solution and silane coupling agent KH550 to modify the interface between the raw materials, optimize the pyrophyllite / nano-titanium dioxide filling system effect, enhance the reinforcing effect of the pyrophyllite / nano-titanium dioxide compounding agent and the system, thereby enhancing the coordination of system performance and optimizing the water resistance and temperature change stability of the system;
[0031] 3. Balancing agent for blending flaky talc powder: flaky talc powder is blended with sodium dodecylbenzene sulfonate and chitosan solution to improve the dispersibility of flaky talc powder and the compatibility between system raw materials. At the same time, nano mica powder and boron nitride are blended with barium nitrate solution and sodium carboxymethyl cellulose, and the blended talc powder is combined with lamellar nano mica powder, and boron nitride is blended and coordinated to optimize the interface between system raw materials, provide easy-to-clean surface and optimize gloss, thereby coordinating and improving the high gloss, stain resistance and antibacterial properties of the product, and optimizing the water resistance and temperature change stability of the product. DETAILED DESCRIPTION
[0032] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] A high-gloss stain-resistant glaze of this embodiment includes the following raw materials in parts by weight:
[0034] 10-15 parts of albite, 8-12 parts of modified quartz powder, 6-9 parts of a balancing agent for blending flaky talc, 5-8 parts of calcite, 4-7 parts of nano alumina, 3-5 parts of nano silicon dioxide, 4-7 parts of nano silver oxide and 10-15 parts of water.
[0035] The preparation method of the modified quartz powder of this embodiment is:
[0036] S11: The quartz powder is first stirred with a sufficient amount of a 5% by mass hydrogen peroxide solution, then washed with boiling water for 2-3 times, then filtered and dried, and preheated at 60-65° C. for 1 hour to obtain pretreated quartz powder;
[0037] S12: adding 1-3 parts by weight of a 4-6% sodium lignin sulfonate solution and 2-4 parts by weight of wollastonite to 6-9 parts by weight of a 5% sodium silicate solution, and then adding 1-2 parts by weight of stearic acid, stirring sufficiently to obtain a wollastonite modified solution;
[0038] S13: Blending 4-7 parts of pretreated quartz powder and 6-10 parts of wollastonite modified liquid by weight, and continuing to stir sufficiently to obtain a quartz-based liquid;
[0039] S14: ultrasonically treat the quartz base liquid and the pyrophyllite / nano-titanium dioxide compounding agent in a weight ratio of 5:3. After the ultrasonic treatment is completed, filter and dry to obtain modified quartz powder.
[0040] The ultrasonic power of the ultrasonic treatment in this embodiment is 450-550W, and the ultrasonic time is 1-2h.
[0041] The preparation method of the pyrophyllite / nano titanium dioxide compounding agent of the present embodiment is:
[0042] According to weight, 5-8 parts of pyrophyllite and 1-3 parts of nano-titanium dioxide are added to 7-9 parts of sodium alginate solution, and then 2-4 parts of calcium nitrate solution and 1-2 parts of silane coupling agent KH550 are added, and the mixture is mixed thoroughly, filtered and dried to obtain a pyrophyllite / nano-titanium dioxide compounding agent.
[0043] The mass fraction of the sodium alginate solution in this embodiment is 4-7%; the mass fraction of the calcium nitrate solution is 2-5%.
[0044] The preparation method of the balancing agent for blending flaky talcum powder in this embodiment is as follows:
[0045] S101: mixing flaky talc, sodium dodecylbenzene sulfonate and chitosan solution in a weight ratio of (3-5):1:(6-8) to obtain a flaky talc solution;
[0046] S102: adding 3-5 parts of nano-mica powder and 2-3 parts of boron nitride to 5-8 parts of barium nitrate solution by weight, and then adding 1-3 parts of sodium carboxymethyl cellulose, and ball milling the mixture at a speed of 1000 r / min for 1 hour. After the ball milling is completed, filtering and drying are performed to obtain a formulation;
[0047] S103: stirring the blending agent and the flaky talc liquid in a weight ratio of 2:5, filtering and drying after the stirring is completed, to obtain a balancing agent for blending the flaky talc.
[0048] The mass fraction of the chitosan solution in this embodiment is 2-5%; the mass fraction of the barium nitrate solution is 4-6%.
[0049] The stirring temperature of the stirring treatment in this embodiment is 60-65° C., the stirring speed is 450-500 r / min, and the stirring time is 30-40 min.
[0050] A method for preparing a high-gloss, stain-resistant ceramic according to the present embodiment comprises the following steps:
[0051] Step 1, weighing raw materials of high-gloss and stain-resistant glaze water according to weight parts, mixing the raw materials of high-gloss and stain-resistant glaze water and subjecting them to ball milling treatment, with a ball milling speed of 1000 r / min, and ball milling for 2 hours, and then completing the ball milling to obtain high-gloss and stain-resistant glaze water;
[0052] Step 2: 10-15 parts of illite, 5-8 parts of kaolin, 4-7 parts of potassium feldspar, 3-5 parts of silicon carbide and 2-5 parts of calcium carbonate are mixed by weight and wet-milled at a ball milling speed of 1500r / min for 2h. After sufficient ball milling, the mixture is put into a mold for molding at a molding pressure of 45-50MPa for 1h to obtain a ceramic body;
[0053] Step 3: glaze the ceramic body with high gloss and stain-resistant glaze water, with a glaze amount of 580g / m 2 Then, it is sintered at 1300°C for 2 hours. After the sintering is completed, a high-gloss and stain-resistant ceramic is obtained.
[0054] The high-gloss stain-resistant ceramic of this embodiment is prepared by the above-mentioned preparation method of the high-gloss stain-resistant ceramic.
[0055] Example 1: A high-gloss stain-resistant glaze comprising the following raw materials in parts by weight:
[0056] 10 parts of albite, 8 parts of modified quartz powder, 6 parts of a balancing agent for blending flaky talc, 5 parts of calcite, 4 parts of nano alumina, 3 parts of nano silicon dioxide, 4 parts of nano silver oxide and 10 parts of water.
[0057] The preparation method of the modified quartz powder of this embodiment is:
[0058] S11: The quartz powder is first stirred with a sufficient amount of 5% by mass hydrogen peroxide solution, then washed twice with boiling water, filtered, dried, and preheated at 60° C. for 1 h to obtain pretreated quartz powder;
[0059] S12: adding 1 part of 4% sodium lignin sulfonate solution and 2 parts of wollastonite to 6 parts of 5% sodium silicate solution by weight, and then adding 1 part of stearic acid, stirring well, to obtain wollastonite modified solution;
[0060] S13: Blending 4 parts of pretreated quartz powder and 6 parts of wollastonite modified liquid by weight, and continuing to stir sufficiently to obtain a quartz-based liquid;
[0061] S14: ultrasonically treat the quartz base liquid and the pyrophyllite / nano-titanium dioxide compounding agent in a weight ratio of 5:3. After the ultrasonic treatment is completed, filter and dry to obtain modified quartz powder.
[0062] The ultrasonic power of the ultrasonic treatment in this embodiment is 450W, and the ultrasonic time is 1 hour.
[0063] The preparation method of the pyrophyllite / nano titanium dioxide compounding agent of the present embodiment is:
[0064] According to weight, 5 parts of pyrophyllite and 1 part of nano-titanium dioxide are added to 7 parts of sodium alginate solution, and then 2 parts of calcium nitrate solution and 1 part of silane coupling agent KH550 are added, and the mixture is mixed thoroughly, filtered and dried to obtain a pyrophyllite / nano-titanium dioxide compounding agent.
[0065] The mass fraction of the sodium alginate solution in this embodiment is 4%; the mass fraction of the calcium nitrate solution is 2%.
[0066] The preparation method of the balancing agent for blending flaky talcum powder in this embodiment is as follows:
[0067] S101: mixing flaky talc, sodium dodecylbenzene sulfonate and chitosan solution in a weight ratio of 3:1:6 to obtain a flaky talc solution;
[0068] S102: adding 3 parts of nano-mica powder and 2 parts of boron nitride to 5 parts of barium nitrate solution by weight, and then adding 1 part of sodium carboxymethyl cellulose, and ball-milling the mixture at a speed of 1000 r / min for 1 hour. After the ball milling is completed, filtering and drying are performed to obtain a formulation;
[0069] S103: stirring the blending agent and the flaky talc liquid in a weight ratio of 2:5, filtering and drying after the stirring is completed, to obtain a balancing agent for blending the flaky talc.
[0070] The mass fraction of the chitosan solution in this embodiment is 2%; the mass fraction of the barium nitrate solution is 4%.
[0071] The stirring temperature of the stirring process in this embodiment is 60° C., the stirring speed is 450 r / min, and the stirring time is 30 min.
[0072] A method for preparing a high-gloss, stain-resistant ceramic according to the present embodiment comprises the following steps:
[0073] Step 1, weighing raw materials of high-gloss and stain-resistant glaze water according to weight parts, mixing the raw materials of high-gloss and stain-resistant glaze water and subjecting them to ball milling treatment, with a ball milling speed of 1000 r / min, and ball milling for 2 hours, and then completing the ball milling to obtain high-gloss and stain-resistant glaze water;
[0074] Step 2: 10 parts of illite, 5 parts of kaolin, 4 parts of potassium feldspar, 3 parts of silicon carbide and 2 parts of calcium carbonate are mixed by wet ball milling at a ball milling speed of 1500r / min for 2h. After sufficient ball milling, the mixture is put into a mold for molding at a molding pressure of 45MPa for 1h to obtain a ceramic body;
[0075] Step 3: glaze the ceramic body with high gloss and stain-resistant glaze water, with a glaze amount of 580g / m 2 Then, it is sintered at 1300°C for 2 hours. After the sintering is completed, a high-gloss and stain-resistant ceramic is obtained.
[0076] The high-gloss stain-resistant ceramic of this embodiment is prepared by the above-mentioned preparation method of the high-gloss stain-resistant ceramic.
[0077] Example 2: A high-gloss stain-resistant glaze comprising the following raw materials in parts by weight:
[0078] 15 parts of albite, 12 parts of modified quartz powder, 9 parts of a balancing agent for blending flaky talc, 8 parts of calcite, 7 parts of nano alumina, 5 parts of nano silicon dioxide, 7 parts of nano silver oxide and 15 parts of water.
[0079] The preparation method of the modified quartz powder of this embodiment is:
[0080] S11: The quartz powder is first stirred with a sufficient amount of 5% by mass hydrogen peroxide solution, then washed with boiling water for 3 times, then filtered and dried, and preheated at 65°C for 1h to obtain pretreated quartz powder;
[0081] S12: Add 3 parts by weight of 6% sodium lignin sulfonate solution and 4 parts of wollastonite to 9 parts by weight of 5% sodium silicate solution, then add 2 parts of stearic acid, stir well, and obtain wollastonite modified solution;
[0082] S13: 7 parts of pretreated quartz powder and 10 parts of wollastonite modified liquid are mixed by weight, and stirred thoroughly to obtain a quartz matrix liquid;
[0083] S14: ultrasonically treat the quartz base liquid and the pyrophyllite / nano-titanium dioxide compounding agent in a weight ratio of 5:3. After the ultrasonic treatment is completed, filter and dry to obtain modified quartz powder.
[0084] The ultrasonic power of the ultrasonic treatment in this embodiment is 550W, and the ultrasonic time is 2h.
[0085] The preparation method of the pyrophyllite / nano titanium dioxide compounding agent of the present embodiment is:
[0086] By weight, 8 parts of pyrophyllite and 3 parts of nano-titanium dioxide were added to 9 parts of sodium alginate solution, followed by adding 4 parts of calcium nitrate solution and 2 parts of silane coupling agent KH550, and the mixture was mixed thoroughly, filtered and dried to obtain a pyrophyllite / nano-titanium dioxide compounding agent.
[0087] The mass fraction of the sodium alginate solution in this embodiment is 7%; the mass fraction of the calcium nitrate solution is 5%.
[0088] The preparation method of the balancing agent for blending flaky talcum powder in this embodiment is as follows:
[0089] S101: mixing flaky talc, sodium dodecylbenzene sulfonate and chitosan solution in a weight ratio of 5:1:8 to obtain a flaky talc solution;
[0090] S102: 5 parts of nano-mica powder and 3 parts of boron nitride are mixed and added to 8 parts of barium nitrate solution, and then 3 parts of sodium carboxymethyl cellulose are added, and the mixture is ball-milled at a speed of 1000 r / min for 1 hour. After the ball-milling is completed, the mixture is filtered and dried to obtain a formulation;
[0091] S103: stirring the blending agent and the flaky talc liquid in a weight ratio of 2:5, filtering and drying after the stirring is completed, to obtain a balancing agent for blending the flaky talc.
[0092] The mass fraction of the chitosan solution in this embodiment is 5%; the mass fraction of the barium nitrate solution is 6%.
[0093] The stirring temperature of the stirring treatment in this embodiment is 65° C., the stirring speed is 500 r / min, and the stirring time is 40 min.
[0094] A method for preparing a high-gloss, stain-resistant ceramic according to the present embodiment comprises the following steps:
[0095] Step 1, weighing raw materials of high-gloss and stain-resistant glaze water according to weight parts, mixing the raw materials of high-gloss and stain-resistant glaze water and subjecting them to ball milling treatment, with a ball milling speed of 1000 r / min, and ball milling for 2 hours, and then completing the ball milling to obtain high-gloss and stain-resistant glaze water;
[0096] Step 2: 15 parts of illite, 8 parts of kaolin, 7 parts of potassium feldspar, 5 parts of silicon carbide and 5 parts of calcium carbonate are mixed and wet-milled by weight at a ball milling speed of 1500 r / min for 2 hours. After sufficient ball milling, the mixture is put into a mold for molding at a molding pressure of 50 MPa for 1 hour to obtain a ceramic body;
[0097] Step 3: glaze the ceramic body with high gloss and stain-resistant glaze water, with a glaze amount of 580g / m 2 Then, it is sintered at 1300°C for 2 hours. After the sintering is completed, a high-gloss and stain-resistant ceramic is obtained.
[0098] The high-gloss stain-resistant ceramic of this embodiment is prepared by the above-mentioned preparation method of the high-gloss stain-resistant ceramic.
[0099] Example 3: A high-gloss stain-resistant glaze comprising the following raw materials in parts by weight:
[0100] 12.5 parts of albite, 10 parts of modified quartz powder, 7.5 parts of a balancing agent for blending flaky talc, 6.5 parts of calcite, 5.5 parts of nano alumina, 4 parts of nano silicon dioxide, 5.5 parts of nano silver oxide and 12.5 parts of water.
[0101] The preparation method of the modified quartz powder of this embodiment is:
[0102] S11: The quartz powder is first stirred with a sufficient amount of 5% by mass hydrogen peroxide solution, then washed twice with boiling water, filtered, dried, and preheated at 62.5°C for 1h to obtain pretreated quartz powder;
[0103] S12: Add 2 parts by weight of 5% sodium lignin sulfonate solution and 3 parts of wollastonite to 7.5 parts by weight of 5% sodium silicate solution, then add 1.5 parts of stearic acid, stir well, and obtain wollastonite modified solution;
[0104] S13: Blending 5.5 parts of pretreated quartz powder and 8 parts of wollastonite modified liquid by weight, and continuing to stir sufficiently to obtain a quartz-based liquid;
[0105] S14: ultrasonically treat the quartz base liquid and the pyrophyllite / nano-titanium dioxide compounding agent in a weight ratio of 5:3. After the ultrasonic treatment is completed, filter and dry to obtain modified quartz powder.
[0106] The ultrasonic power of the ultrasonic treatment in this embodiment is 500 W, and the ultrasonic time is 1.5 h.
[0107] The preparation method of the pyrophyllite / nano titanium dioxide compounding agent of the present embodiment is:
[0108] According to weight, 6.5 parts of pyrophyllite and 2 parts of nano-titanium dioxide are added to 8 parts of sodium alginate solution, followed by adding 3 parts of calcium nitrate solution and 1.5 parts of silane coupling agent KH550, and the mixture is mixed thoroughly, filtered and dried to obtain a pyrophyllite / nano-titanium dioxide compounding agent.
[0109] The mass fraction of the sodium alginate solution in this embodiment is 5.5%; the mass fraction of the calcium nitrate solution is 3.5%.
[0110] The preparation method of the balancing agent for blending flaky talcum powder in this embodiment is as follows:
[0111] S101: mixing flaky talc, sodium dodecylbenzene sulfonate and chitosan solution in a weight ratio of 4:1:7 to obtain a flaky talc solution;
[0112] S102: 4 parts of nano-mica powder and 2.5 parts of boron nitride are mixed and added to 6.5 parts of barium nitrate solution, and then 2 parts of sodium carboxymethyl cellulose are added, and the mixture is ball-milled at a speed of 1000 r / min for 1 hour. After the ball-milling is completed, the mixture is filtered and dried to obtain a formulation;
[0113] S103: stirring the blending agent and the flaky talc liquid in a weight ratio of 2:5, filtering and drying after the stirring is completed, to obtain a balancing agent for blending the flaky talc.
[0114] The mass fraction of the chitosan solution in this embodiment is 3.5%; the mass fraction of the barium nitrate solution is 5%.
[0115] The stirring temperature of the stirring process in this embodiment is 62° C., the stirring speed is 470 r / min, and the stirring time is 35 min.
[0116] A method for preparing a high-gloss, stain-resistant ceramic according to the present embodiment comprises the following steps:
[0117] Step 1, weighing raw materials of high-gloss and stain-resistant glaze water according to weight parts, mixing the raw materials of high-gloss and stain-resistant glaze water and subjecting them to ball milling treatment, with a ball milling speed of 1000 r / min, and ball milling for 2 hours, and then completing the ball milling to obtain high-gloss and stain-resistant glaze water;
[0118] Step 2: 12.5 parts of illite, 6.5 parts of kaolin, 5.5 parts of potassium feldspar, 4 parts of silicon carbide and 3.5 parts of calcium carbonate are mixed by weight and wet-milled at a speed of 1500 r / min for 2 hours. After sufficient ball milling, the mixture is put into a mold for molding at a molding pressure of 47.5 MPa for 1 hour to obtain a ceramic body;
[0119] Step 3: glaze the ceramic body with high gloss and stain-resistant glaze water, with a glaze amount of 580g / m 2 Then, it is sintered at 1300°C for 2 hours. After the sintering is completed, a high-gloss and stain-resistant ceramic is obtained.
[0120] The high-gloss stain-resistant ceramic of this embodiment is prepared by the above-mentioned preparation method of the high-gloss stain-resistant ceramic.
[0121] Comparative Example 1:
[0122] The difference from Example 3 is that no modified quartz powder is added.
[0123] Comparative Example 2:
[0124] The difference from Example 3 is that no quartz matrix liquid is added in the preparation of the modified quartz powder.
[0125] Comparative Example 3:
[0126] The difference from Example 3 is that no wollastonite modifying liquid is added to the quartz matrix liquid.
[0127] Comparative Example 4:
[0128] The difference from Example 3 is that no sodium lignin sulfonate solution or wollastonite is added to the wollastonite modified liquid.
[0129] Comparative Example 5:
[0130] The difference from Example 3 is that no pretreated quartz powder is added to the quartz matrix liquid.
[0131] Comparative Example 6:
[0132] The difference from Example 3 is that no pyrophyllite / nano-titanium dioxide compounding agent is added in the preparation of the modified quartz powder.
[0133] Comparative Example 7:
[0134] The difference from Example 3 is that no pyrophyllite is added to the pyrophyllite / nano-titanium dioxide compounding agent.
[0135] Comparative Example 8:
[0136] The difference from Example 3 is that nano titanium dioxide is not added to the pyrophyllite / nano titanium dioxide compounding agent.
[0137] Comparative Example 9:
[0138] The difference from Example 3 is that no calcium nitrate solution and silane coupling agent KH550 are added to the pyrophyllite / nano-titanium dioxide compounding agent.
[0139] Comparative Example 10:
[0140] The difference from Example 3 is that no balancing agent for blending flaky talc is added.
[0141] Comparative Example 11:
[0142] The difference from Example 3 is that no flaky talc liquid is added in the preparation of the balancing agent for blending the flaky talc.
[0143] Comparative Example 12:
[0144] The difference from Example 3 is that no blending agent is added in the preparation of the balancing agent for blending the flaky talc.
[0145] Comparative Example 13:
[0146] The difference from Example 3 is that no nano mica powder is added to the formulation.
[0147] Comparative Example 14:
[0148] The difference from Example 3 is that no boron nitride is added to the formulation.
[0149] Comparative Example 15:
[0150] The difference from Example 3 is that sodium carboxymethyl cellulose is not added to the formulation, and the barium nitrate solution is replaced by water.
[0151] The ceramic products prepared in Examples 1 to 3 and Comparative Examples 1 to 15 were subjected to conventional antibacterial, glossiness and antifouling performance tests. The test results are shown in Table 1.
[0152] Table 1 Performance test results of ceramic products of Examples 1 to 3 and Comparative Examples 1 to 15:
[0153]
[0154] It can be seen from comparative examples 1 to 15 and embodiments 1 to 3 that the ceramic product of embodiment 3 has an excellent antibacterial rate for Escherichia coli and a significant antibacterial durability effect. At the same time, the ceramic product has excellent gloss and anti-fouling grade performance. The antibacterial, gloss and anti-fouling properties of the ceramic product can achieve coordinated improvements.
[0155] The ceramic products prepared in Examples 1 to 3 and Comparative Examples 1 to 15 were immersed in 45°C water for 6 hours, then taken out, naturally dried, and then heated to 70°C at a rate of 3°C / min, kept warm for 12 hours, and finally placed at -5°C for 12 hours. Conventional antibacterial, glossiness and anti-fouling performance tests were then carried out, and the water resistance and temperature change stability of the ceramic products were tested. The test results are shown in Table 2.
[0156] Table 2 Performance test results of the ceramic products of Examples 1 to 3 and Comparative Examples 1 to 15 under water immersion and temperature change conditions:
[0157]
[0158] It can be seen from Comparative Examples 1 to 15 and Example 3 that the product of Example 3 has significant antibacterial, glossiness and antifouling performance stability under water immersion and temperature change conditions, indicating that the product has good water resistance and temperature change resistance stability;
[0159] It can be seen from Comparative Example 1, Comparative Example 10 and Example 3 that without adding modified quartz powder and balancing agent for blending flaky talc, the performance stability of the product deteriorates significantly. The synergistic effect of the two is the most obvious.
[0160] As can be seen from Comparative Examples 2 to 6 and Example 3, the performance of the products has a trend of varying degrees of deterioration when no quartz matrix liquid is added in the preparation of the modified quartz powder, no wollastonite modifying liquid is added to the quartz matrix liquid, no sodium lignin sulfonate solution and wollastonite are added to the wollastonite modifying liquid, no pretreated quartz powder is added to the quartz matrix liquid, and no pyrophyllite / nano-titanium dioxide compounding agent is added in the preparation of the modified quartz powder. At the same time, the performance of the product is significantly deteriorated when no pyrophyllite / nano-titanium dioxide compounding agent is added. The quartz matrix liquid prepared by the wollastonite modifying liquid obtained by the method of the present invention has the most significant product performance effect.
[0161] As can be seen from Comparative Examples 7 to 9 and Example 3, the pyrophyllite / nano-titanium dioxide compounding agent was not added with pyrophyllite, the pyrophyllite / nano-titanium dioxide compounding agent was not added with nano-titanium dioxide, and the pyrophyllite / nano-titanium dioxide compounding agent was not added with calcium nitrate solution and silane coupling agent KH550. The performance of the product also has different deterioration trends. The pyrophyllite / nano-titanium dioxide compounding agent obtained by the specific method of the present invention has the most obvious performance effect of the product;
[0162] It can be seen from Comparative Examples 11 to 15 and Example 3 that when no flaky talc liquid is added in the preparation of the balancing agent for blending flaky talc, and no formulating agent is added in the preparation of the balancing agent for blending flaky talc, the performance of the product tends to deteriorate. When no nano-mica powder is added to the formulating agent, no boron nitride is added to the formulating agent, no sodium carboxymethyl cellulose is added to the formulating agent, and the barium nitrate solution is replaced by water, the performance of the product also tends to deteriorate to varying degrees. The balancing agent for blending flaky talc obtained by the formulating agent obtained by the specific method of the present invention and the flaky talc liquid has the most significant performance effect, and the replacement by other methods is not as obvious as the effect of the present invention.
[0163] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0164] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A high-gloss, stain-resistant glaze, characterized in that: It includes the following raw materials in parts by weight: 10-15 parts of albite, 8-12 parts of modified quartz powder, 6-9 parts of a balancing agent for blending flaky talc, 5-8 parts of calcite, 4-7 parts of nano-alumina, 3-5 parts of nano-silicon dioxide, 4-7 parts of nano-silver oxide and 10-15 parts of water; The preparation method of the modified quartz powder is: S11: The quartz powder is first stirred with a sufficient amount of a 5% by mass hydrogen peroxide solution, then washed with boiling water for 2-3 times, then filtered and dried, and preheated at 60-65° C. for 1 hour to obtain pretreated quartz powder; S12: adding 1-3 parts by weight of a 4-6% sodium lignin sulfonate solution and 2-4 parts by weight of wollastonite to 6-9 parts by weight of a 5% sodium silicate solution, and then adding 1-2 parts by weight of stearic acid, stirring sufficiently to obtain a wollastonite modified solution; S13: Blending 4-7 parts of pretreated quartz powder and 6-10 parts of wollastonite modified liquid by weight, and continuing to stir sufficiently to obtain a quartz-based liquid; S14: ultrasonically treating the quartz base liquid and the pyrophyllite / nano-titanium dioxide compounding agent in a weight ratio of 5:3, filtering and drying after the ultrasonic treatment to obtain a modified quartz powder; The preparation method of the pyrophyllite / nano titanium dioxide compounding agent is: According to weight, 5-8 parts of pyrophyllite and 1-3 parts of nano-titanium dioxide are added to 7-9 parts of sodium alginate solution, and then 2-4 parts of calcium nitrate solution and 1-2 parts of silane coupling agent KH550 are added, and the mixture is mixed thoroughly, and then filtered and dried to obtain a pyrophyllite / nano-titanium dioxide compounding agent; The preparation method of the balancing agent for blending flaky talcum powder is as follows: S101: mixing flaky talc, sodium dodecylbenzene sulfonate and chitosan solution in a weight ratio of (3-5):1:(6-8) to obtain a flaky talc solution; S102: adding 3-5 parts of nano-mica powder and 2-3 parts of boron nitride to 5-8 parts of barium nitrate solution by weight, and then adding 1-3 parts of sodium carboxymethyl cellulose, and ball milling the mixture at a speed of 1000 r / min for 1 hour. After the ball milling is completed, filtering and drying are performed to obtain a formulation; S103: stirring the blending agent and the flaky talc liquid in a weight ratio of 2:5, filtering and drying after the stirring is completed, to obtain a balancing agent for blending the flaky talc.
2. The high-gloss stain-resistant glaze according to claim 1, characterized in that: The ultrasonic power of the ultrasonic treatment is 450-550W, and the ultrasonic time is 1-2h.
3. The high-gloss stain-resistant glaze according to claim 1, characterized in that: The mass fraction of the sodium alginate solution is 4-7%.
4. The high-gloss stain-resistant glaze according to claim 1, characterized in that: The mass fraction of the calcium nitrate solution is 2-5%.
5. The high-gloss stain-resistant glaze according to claim 1, characterized in that: The mass fraction of the chitosan solution is 2-5%.
6. The high-gloss stain-resistant glaze according to claim 1, characterized in that: The mass fraction of the barium nitrate solution is 4-6%.
7. The high-gloss stain-resistant glaze according to claim 1, characterized in that: The stirring temperature of the stirring treatment is 60-65° C., the stirring speed is 450-500 r / min, and the stirring time is 30-40 min.
8. A method for preparing high-gloss stain-resistant ceramics, using the high-gloss stain-resistant glaze according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1, weighing raw materials of high-gloss and stain-resistant glaze water according to weight parts, mixing the raw materials of high-gloss and stain-resistant glaze water and subjecting them to ball milling treatment, with a ball milling speed of 1000 r / min, and ball milling for 2 hours, and then completing the ball milling to obtain high-gloss and stain-resistant glaze water; Step 2: 10-15 parts of illite, 5-8 parts of kaolin, 4-7 parts of potassium feldspar, 3-5 parts of silicon carbide and 2-5 parts of calcium carbonate are mixed by weight and wet-milled at a ball milling speed of 1500r / min for 2h. After sufficient ball milling, the mixture is put into a mold for molding at a molding pressure of 45-50MPa for 1h to obtain a ceramic body; Step 3: glaze the ceramic body with high gloss and stain-resistant glaze water, with a glaze amount of 580g / m 2 Then, it is sintered at 1300°C for 2 hours. After the sintering is completed, a high-gloss and stain-resistant ceramic is obtained.
9. A high-gloss stain-resistant ceramic prepared by the method for preparing the high-gloss stain-resistant ceramic according to claim 8.
Citation Information
Patent Citations
Glaze water, preparation process thereof and method for preparing high-temperature strengthened domestic porcelain by using glaze water
CN112645595A
Underglaze blue glaze water, underglaze blue ceramic and preparation method of underglaze blue ceramic
CN119038954A